2009
DOI: 10.4028/www.scientific.net/jnanor.5.169
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of Zinc Aluminate Nanostructured Material

Abstract: We have used zinc aluminate nanostructured films deposited by spray pyrolysis to determine its biocompatibility assessed by cells attachment and cell differentiation. Cell attachment onto zinc aluminate showed an increase of 53, 81 and 86% at 180, 300 and 420 minutes (p<0.05) when compared to controls. Mineralization was analyzed at 5 and 14 days of culture by scanning electron microscopy, microanalysis and atomic force microscopy. Our results showed in experimental culture a higher density of mineral-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It was recently demonstrated that zinc‐based or doped ceramics are able to increase osteoblasts proliferation, biomineralization, and bone formation 18. The ZnAl 2 O 4 spinel compound showed a good biological response with regards to attachment and viability, with good cell morphology adhered to the semi‐spherical grains of the ceramic 19, 20. Nanoporous spinel may therefore be easily integrated for such applications.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently demonstrated that zinc‐based or doped ceramics are able to increase osteoblasts proliferation, biomineralization, and bone formation 18. The ZnAl 2 O 4 spinel compound showed a good biological response with regards to attachment and viability, with good cell morphology adhered to the semi‐spherical grains of the ceramic 19, 20. Nanoporous spinel may therefore be easily integrated for such applications.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigations have focused on the development of biphasic calcium phosphate composites containing alumina, as they can present improved mechanical properties, biocompatibility and bone formation in combination with adjacent hard tissues [13]. Zinc oxide presents antibacterial ability and biocompatibility [14] allowing for the design of engineered zinc-containing ceramic composites for bone tissue repair, and it has the following benefits: (i) the presence of apatite in tricalcium Zn-phosphate may induce cell proliferation [15], and (ii) it can stimulate osteoblast cells in aluminate-based materials, favoring the mineralization process [16].…”
Section: Introductionmentioning
confidence: 98%
“…In addition, zinc based or doped ceramics are believed to be nontoxic, biocompatible and they have shown to be capable of increasing osteoblasts proliferation, stimulated bone cell differentiation and manifest stimulatory effects on bone formation both in vitro and in vivo, when zinc was incorporated into implanted material [26][27][28][29] . Biological applications of ZnAl 2 O 4 ceramic films has been evaluated previously, based on cell culture tests using a human gingival fibroblasts transfected with CEMP1 gene, which let the cell adhesion maintenance and increasing the expression of bone-related molecules with a good mineralization process onto zinc aluminate nanostructured films 30 . Based on all previous results, it would be of great interest to understand new mechanisms to produce nontoxic and biocompatible zinc based ceramics materials, because almost there is not information about the role of zinc aluminate on the osteoblasts behavior.…”
Section: Introductionmentioning
confidence: 99%